Ectopic expression of mitochondrial gamma carbonic anhydrase 2 causes male sterility by anther indehiscence - Villarreal, Fernando (2009)
Plant mitochondria include gamma-type carbonic anhydrases (γCAs) of unknown function. In Arabidopsis, the γCAs form a gene family of five members which all are attached to the NADH dehydrogenase complex (complex I) of the respiratory chain. Here we report a functional analysis of gamma carbonic anhydrase 2 (CA2). The gene encoding CA2 is constitutively expressed in all plant organs investigated but it is ten fold induced in flowers, particularly in tapetal tissue. Ectopic expression of CA2 in Arabidopsis causes male sterility in transgenic plants. In normal anther development, secondary thickenings of the endothecial cell wall cause anthers to open upon dehydration. Histological analyses revealed that abnormal secondary thickening prevents anther opening in 35S::CA2 transgenic plants. CA2 abundance in transgenic plants is increased 2–3 fold compared to wild-type plants as revealed by Western blotting analyses. Moreover, abundance of other members of the CA family, termed CA3 and CAL2, is increased in transgenic plants. Oxygen uptake measurements revealed that respiration in transgenic plants is mainly based on NADH reduction by the alternative NADH dehydrogenases present in plant mitochondria. Furthermore, the formation of reactive oxygen species (ROS) is very low in transgenic plants. We propose that reduction in ROS inhibits H2O2 dependent lignin polymerization in CA2 over-expressing plants, thereby causing male sterility.